2020
DOI: 10.1093/molbev/msaa140
|View full text |Cite
|
Sign up to set email alerts
|

Khoe-San Genomes Reveal Unique Variation and Confirm the Deepest Population Divergence in Homo sapiens

Abstract: The southern African indigenous Khoe-San populations harbor the most divergent lineages of all living peoples. Exploring their genomes is key to understanding deep human history. We sequenced 25 full genomes from five Khoe-San populations, revealing many novel variants, that 25% of variants are unique to the Khoe-San, and that the Khoe-San group harbors the greatest level of diversity across the globe. In line with previous studies, we found several gene regions with extreme values in genome-wide scans for sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 48 publications
(84 reference statements)
8
85
0
Order By: Relevance
“…The fact that the precuneus in its current form is, however, already visible in the palaeoneurological record from1 00 ka during the MSA, reveals a different scenario. Also, initial work on the genomes of living Khoe-San and ancient hunter-gatherer populations from southern Africa indicates selection for brain-selective gene regions associated with neuron connectivity at more than 300 ka (Schlebusch et al 2020). Based on what we presented here as part of our four-field co-evolutionary exploration, we suggest that the current evidence supports a scenario of long-term, incremental physiological, neurological, genetic, and socio-technical developments that gave rise to the sapient mind since the H. sapiens-Neanderthal split several hundred thousand years ago, instead of an abrupt appearance post-50 ka.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that the precuneus in its current form is, however, already visible in the palaeoneurological record from1 00 ka during the MSA, reveals a different scenario. Also, initial work on the genomes of living Khoe-San and ancient hunter-gatherer populations from southern Africa indicates selection for brain-selective gene regions associated with neuron connectivity at more than 300 ka (Schlebusch et al 2020). Based on what we presented here as part of our four-field co-evolutionary exploration, we suggest that the current evidence supports a scenario of long-term, incremental physiological, neurological, genetic, and socio-technical developments that gave rise to the sapient mind since the H. sapiens-Neanderthal split several hundred thousand years ago, instead of an abrupt appearance post-50 ka.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Some of the genes in their list affect neurons, brain growth and cognition, and one of them (ADSL) has recently been identified as selected for in H. sapiens after our divergence from Neanderthals (Stepanova et al 2020). Based on the genomes of living and ancient Khoe-San populations from southern Africa, Schlebusch et al (2020) found new variations in early H. sapiens subsequent to their split from the Neanderthals, but before their split from other African populations at more than 300 ka. These findings include a brainrelated region of the LPHN3 gene on chromosome 4, which plays an important role in determining the connectivity rates between the principal neurons of the cortex.…”
Section: Grade 7 Causal Network Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…S8). This study also identifies a large set of old variants, well before 300kya, associated with genes belonging to putative positively-selected regions before the deepest divergence of Homo sapiens populations [34], such as LPHN3, FBXW7, and COG5 (figure S9).…”
Section: Variant Subset Distributionsmentioning
confidence: 90%
“…Such phenotypes include energy storage and enhanced use of metabolic water, reduced nonrenal water loss, low energy expenditure, ability to cope with high-salt diets without developing hypertension, adaptive tolerance to starvation and dehydration, and decreased renal water loss (Box 1 and Figure 1D). Some studies additionally identified functional categories of genes involved in stress responses (oxidative stress, DNA damage and repair, and heat stress) [13,18,32], response to radiation [32,56], dust ingestion [32], and toxic diets (perception of bitter taste [18] and xenobiotic metabolism [17,32,57]) as targets of natural selection, suggesting other biological adaptations that have not been explicitly targeted in phenotypic studies.…”
Section: Convergent Evolution At the Genetic Levelmentioning
confidence: 99%